Prevalence of idiopathic scoliosis in girls with central precocious puberty: effect of a gonadotropin-releasing hormone agonist - Lindsey Yoojin Chung (Annals of Pediatric Endocrinology & Metabolism, 2020)
Purpose Adolescent idiopathic scoliosis (AIS) is the most common form of scoliosis and occurs in children between 10 to 18 years old, during periods of growth spurts and puberty changes. In patients with central precocious puberty (CPP), due to early growth spurt, AIS is expected to develop before 10 years of age. Both AIS and CPP are more common in girls than in boys. The aim of this study was to determine the prevalence of AIS in girls with CPP and to evaluate the effect of treatment with gonadotropin-releasing hormone (GnRH) agonists on progression of scoliosis in these patients. Methods We retrospectively reviewed medical records of 553 girls, 338 with CPP and 215 without CPP. Scoliosis angle was measured on the standing frontal radiograph of each patient according to the Cobb method. Patients with a Cobb angle of 10° or more were diagnosed with scoliosis. For girls with CPP, follow-up spine radiographs were collected 1 year after treatment with GnRH agonists. Progression of scoliosis before and after treatment was compared in terms of Cobb angle changes. Results AIS was more prevalent in girls that were affected by CPP compared tocontrols without CPP (11.5% vs. 6.0%, CPP girls vs. non-CPP girls, respectively, P=0.031). The peak serum luteinizing hormone level positively correlated with Cobb angle (R2=0.015, P=0.023) in the CPP group. No progression of scoliosis was observed in CPP girls after one year of GnRH agonist treatment. Additionally, the prevalence of scoliosis decreased in CPP girls after 1 year of the treatment. Conclusions We report that the prevalence of AIS is higher in girls with CPP than in non-CPP patients. A regular follow-up schedule for spine radiographs should be considered to reduce the risk of progression. Furthermore, GnRH agonist treatment for CPP may have a suppressive effect on progression of AIS.